Effects of puerarin on blood lipids and inflammatory factors in rats with lower limb arteriosclerosis obliterans - LI,Bo (2017)
Abstract This study investigated the effects of puerarin (PUE) on blood lipid and inflammatory factor levels in rats with lower limb arteriosclerosis obliterans (ASO). Sixty rats were randomly divided into control, model, simvastatin, low-PUE, middle-PUE and high-dose PUE group. The animals in later 5 groups were with lower limb ASO, and the later 4 groups were given 1 mg/kg simvastatin and 5, 10 and 20 mg/kg PUE, respectively. The blood lipid and inflammatory factor levels were determined. Results showed that, the serum total cholesterol (TC), triglyceride (TG), low-density lipoprotein cholesterol (LDL-C), interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α) and high-sensitivity C-reactive protein (hs-CRP) level in model group were significantly increased (P <0.01), while the high-density lipoprotein cholesterol (HDL-C) was significantly decreased (P <0.01). Compared with model group, TC, TG, LDL-C, IL-6, TNF-α and hs-CRP in high-dose PUE and simvastatin group were significantly decreased (P <0.01 or P <0.05), and HDL level was significantly increased (P <0.01 or P <0.05). There was no significant difference of each index between simvastatin and high-dose PUE group (P >0.05). PUE can obviously decrease the blood lipid and inflammatory factor levels in rats with lower limb ASO.